Genome-wide analysis uncovers tomato leaf lncRNAs transcriptionally active upon Pseudomonas syringae pv. tomato challenge - Rosli, Hernan Guillermo (2021)
Plants rely on (in)direct detection of bacterial pathogens through plasma membrane-localized and intracellular receptor proteins. Surface pattern-recognition receptors (PRRs) participate in the detection of microbe-associated molecular patterns (MAMPs) and are required for the activation of pattern-triggered immunity (PTI). Pathogenic bacteria, such as Pseudomonas syringae pv. tomato (Pst) deploys ~ 30 effector proteins into the plant cell that contribute to pathogenicity. Resistant plants are capable of detecting the presence or activity of effectors and mount another response termed effector-triggered immunity (ETI). In order to investigate the involvement of tomato’s long non-coding RNAs (lncRNAs) in the immune response against Pst, we used RNA-seq data to predict and characterize those that are transcriptionally active in leaves challenged with a large set of treatments. Our prediction strategy was validated by sequence comparison with tomato lncRNAs described in previous works and by an alternative approach (RT-qPCR). Early PTI (30 min), late PTI (6 h) and ETI (6 h) differentially expressed (DE) lncRNAs were identified and used to perform a co-expression analysis including neighboring (± 100 kb) DE protein-coding genes. Some of the described networks could represent key regulatory mechanisms of photosynthesis, PRR abundance at the cell surface and mitigation of oxidative stress, associated to tomato-Pst pathosystem.